Ultrasonic transmission-mode tomography imaging for liquid/gas two-phase flow - Rahiman, Mohd. Hafiz Fazalul; Abdul Rahim, Ruzairi; Rahiman, Mohd. Hezri Fazalul; Tajjudin, Mazidah (IEEE, 2006)
This paper details the development of noninvasive ultrasonic tomography for imaging liquid and gas flow. The transmission- mode approach has been used for sensing the liquid/ gas two-phase flow, which is a kind of strongly inhomogeneous medium. Sixteen pairs of ultrasonic sensors have been used. By using low excitation voltage of 20 V, fan-shaped beam ultrasonic transmitters will emit ultrasonic pulses to the receivers. The investigations were based on the transmission and the reception of ultrasonic sensors that were mounted circularly on the surface of the experimental vessel. The algorithms used to reconstruct the concentration profile for two-phase flow using a fan-shaped beam scanning geometry were presented. By using a hybridbinary reconstruction algorithm, real-time ultrasonic transmission- mode tomography has been developed. Experiments show that performance is acceptable with an image-reconstruction speed of 10 frames/s. The results of the experiments and possible future improvements were also discussed